2019
DOI: 10.3389/fimmu.2019.01554
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 Deletion Enhances the Anti-inflammatory Potential of GC-Mediated GR Activation During Inflammation

Abstract: The suppression of activated pro-inflammatory macrophages during immune response has a major impact on the outcome of many inflammatory diseases including sepsis and rheumatoid arthritis. The pro- and anti-inflammatory functions of macrophages have been widely studied, whereas their regulation under immunosuppressive treatments such as glucocorticoid (GC) therapy is less well-understood. GC-mediated glucocorticoid receptor (GR) activation is crucial to mediate anti-inflammatory effects. In addition, the anti-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 67 publications
6
19
1
1
Order By: Relevance
“…53 Interestingly, it was recently demonstrated in mouse primary macrophages that the cyclin-dependent kinase 5 (Cdk5) deletion induces the expression of MKP-1. 54 Therefore, GC-dependent inhibition of iNOS can be enhanced by simultaneously targeting Cdk5. 54 These data should be confirmed in mouse models to verify whether GCs combined with specific Cdk inhibitors may have a synergistic immunosuppressive effect.…”
Section: Myeloid Cells Are the Main Targets Of Gcs For Restoring Homementioning
confidence: 99%
See 1 more Smart Citation
“…53 Interestingly, it was recently demonstrated in mouse primary macrophages that the cyclin-dependent kinase 5 (Cdk5) deletion induces the expression of MKP-1. 54 Therefore, GC-dependent inhibition of iNOS can be enhanced by simultaneously targeting Cdk5. 54 These data should be confirmed in mouse models to verify whether GCs combined with specific Cdk inhibitors may have a synergistic immunosuppressive effect.…”
Section: Myeloid Cells Are the Main Targets Of Gcs For Restoring Homementioning
confidence: 99%
“…54 Therefore, GC-dependent inhibition of iNOS can be enhanced by simultaneously targeting Cdk5. 54 These data should be confirmed in mouse models to verify whether GCs combined with specific Cdk inhibitors may have a synergistic immunosuppressive effect. Low-dose GCs in combination with Cdk inhibitors may indeed replace high-dose GC therapy, which has severe side effects, in the treatment of inflammatory diseases.…”
Section: Myeloid Cells Are the Main Targets Of Gcs For Restoring Homementioning
confidence: 99%
“…Consistently, we also showed that roscovitine reversed LPS-induced synaptic loss in the hippocampus. On the other hand, roscovitine is a Cdk5 inhibitor and is reported to have other effects such as anti-inflammatory property [ 34 ]. Thus, in addition to unregulated pSynGAP1, other mechanisms might also be involved in the beneficial effects of roscovitine for sepsis survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In isolated peritoneal macrophages, ( R )-roscovitine inhibited NO production, iNOS, and COX-2 upregulation, and NFκB activation induced by LPS stimulation [ 163 ]. In mice bone-marrow-derived macrophage (BMDM) culture stimulated with LPS, ( R )-roscovitine treatment decreased Il-1β, Il-6, and iNOS mRNA and protein levels [ 164 ]. In murine RAW264.7 macrophages culture stimulated by LPS, ( R )-roscovitine inhibited cell proliferation and diminished nitric oxide production and IL1b, IL6, TNFα, and iNOS expression [ 163 , 164 , 165 ].…”
Section: Effects Of Roscovitine On Leucocytesmentioning
confidence: 99%